Naming violence from the symbolic: Contributions for communication with a feminist approach - Palma-Chacón, Jimena (2023)
This article explores forms of communication that seek to question and reconsider how expressions of violence and femicide are communicated, understanding the power that communicative language has to modify how perception, sensitivity and positioning are understood and constructed by people; thus, cyberactivism and communication strategies used by the collective Ni Una Menos-Costa Rica are explored